2012
DOI: 10.1177/0267659112442902
|View full text |Cite
|
Sign up to set email alerts
|

Central venous saturation is not an alternative to mixed venous saturation during cardiopulmonary bypass in coronary artery surgery patients

Abstract: Although mean biases between the measurements were low, limits of agreement were too large to provide a clinically acceptable estimation of SvO(2) by ScvO(2) in these conditions. Variations in regional oxygen consumption seem to be the main factor worsening the relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The 20-minute data extraction periods in this study were specifically chosen to represent perioperative time points that usually are without considerable circulatory instability. Central and mixed venous oxygen saturation have not shown interchangeability [ 46 48 ] but some studies have suggested that trends in ScvO 2 can replace SvO 2 [ 49 51 ]. During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 20-minute data extraction periods in this study were specifically chosen to represent perioperative time points that usually are without considerable circulatory instability. Central and mixed venous oxygen saturation have not shown interchangeability [ 46 48 ] but some studies have suggested that trends in ScvO 2 can replace SvO 2 [ 49 51 ]. During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…(30, 47) The 20-minute data extraction periods in this study were specifically chosen to represent perioperative time points that usually are without considerable circulatory instability. Central and mixed venous oxygen saturation have not shown interchangeability(48-50) but some studies have suggested that trends in ScvO 2 can replace SvO 2 . (51-53) During stable intraoperative conditions, oxygen content difference is not expected to vary to a large extent whereas cardiac output can show considerable in- and between patient variability.…”
Section: Discussionmentioning
confidence: 99%
“…Alshaer et al [8] examined the correlation during beating heart coronary surgery and concluded that SvO 2 and ScvO 2 are not interchangeable numerically but ScvO 2 can be useful if used as a trend. Soussi et al [9] concluded that central venous saturation can not be an alternative to mixed venous saturation during cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies evaluating the relationship between ScvO 2 and SvO 2 showed a significant variation in results because of different study designs and clinical setup which included intensive care patients with either sepsis, heart failure, or shock [4][5][6][7]. Studies involving such relationship during and after cardiac surgery [8][9][10][11][12][13][14][15] also showed contradicting results, this controversy is generating confusion among clinicians and further work is needed to explore this area.…”
Section: Introductionmentioning
confidence: 99%